Does My Child Have a Developmental Delay? : a Step-by-Step Guide for Parents on Early Intervention. - Vanover, Sarah (Rowman & Littlefield Publishers, 2018)
This book takes parents through the progression of a developmental referral, the evaluation process, the benefits of early intervention, and the roles of the teachers and therapists on the child's support team. It includes personal stories from families who have been through the early intervention process.